The Political Economy of Social Protection in Mozambique - Buur, Lars; Salimo, Padil (SSRN Electronic Journal, 2018)
In the view of international donors, multilateral organisations and government officials, social protection in Mozambique benefits from strong government commitment to it. Their argument is that, in contrast to many African countries, the government has demonstrated a level of commitment and support to social protection that is quite unprecedented. This view relies on the fact that more than 90 per cent of the budget allocated to the implementation of social protection programmes comes from the state budget and that, even within the complex context of the financial crisis that has devastated the economy since 2013, social protection has continued to receive special attention from the government in its budget allocations. Based on a political economy analysis, this paper challenges the common narrative of social protection in Mozambique, by arguing that social protection has been used as a means to mobilise resources from international agencies, in order to ensure the political survival of the Frelimo government. The paper argues that government support of social protection emerged as a reaction to the poor performance of poverty-reduction initiatives, becoming also a mechanism to overcome social protests after the 2008 and 2010 riots in Mozambique, which threatened to jeopardise the stability of the regime and its reproduction of power.
Keywords: *indexed; *tagged; Ethnographic Studies; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Social Protection PEA; development partners / parceiros de cooperação; social protection / proteção social

Decreto n.º 47/2018 - República de Moçambique (Boletim da República, 2018)
Decreto n.º 47/2018: Concernente à revisão dos Programas de Segurança Social Básica, criados pelo Decreto n.º 52/2011, de 12 de Outubro e revoga o Decreto n.º 52/2011, de 12 de Outubro.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; Social security / segurança social; law / direito; social protection / proteção social

Mozambique's social protection system: an overview of the Basic Social Subsidy Programme (PSSB), the Direct Social Action Programme (PASD), the Productive Social Action Programme (PASP) and the Social Assistance Services (PAUS) - Arruda, Pedro (International Policy Centre for Inclusive Growth, 2018)
Mozambique has four main social protection responses in place, including a cash transfer programme (the Basic Social Subsidy Programme—PSSB), a food voucher and in-kind transfer programme (Direct Social Action Programme—PASD), a public works programme (Productive Social Action Programme—PASP), and a set of institutional care services for vulnerable adults, elderly people and children without a home (Social Assistance Services—PAUS). We open this brief with an analysis of relevant social protection policies in Mozambique, followed by a description of the institutional set-up of the Mozambican social protection system. The following section discusses the core features of each of the country’s four flagship social policies, assessing the scale of these programmes and how they relate to each other. In the conclusion, we recall previous critiques regarding the excessive amount of categorical criteria mediating eligibility for these Mozambican social protection initiatives. We make the case for expediting the implementation of the recently developed management and information system—e-INAS—in the hope that it will integrate the databases of the flagship social protection initiatives and increase their reach. Most importantly, we question whether the active search for beneficiaries by health workers contributes to the equity of the PASD, and propose impact evaluation studies for the country’s flagship social programmes, which can lead to a rational revamping of the entire social protection system.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; social protection / proteção social

Programa Conjunto das Nações Unidas para a Protecção Social em Moçambique 2017-2020 - Ministério do Género, Criança e Acção Social - Governo de Moçambique (Ministério do Género, Criança e Acção Social - Governo de Moçambique, 2018)
A Protecção Social é amplamente reconhecida como um conjunto efectivo de intervenções políticas para reduzir a pobreza, a vulnerabilidade a desigualdade e promover o crescimento económico inclusivo. Na última década, o sistema de Protecção Social Básica de Moçambique consolidou-se com a Estratégia Nacional de Segurança Social 2010-2014, todavia o sector ainda permanece fragmentado. A Estratégia Nacional de Segurança Social básica 2016-2024 (ENSSB II), que cobre o período de, aprovada pelo Conselho de Ministros em Fevereiro de 2016 oferece uma oportunidade única para abordar a fragmentação e alinhar melhor as partes envolvidas na materialização de um conjunto ambicioso de metas. A Estratégia tem quatro objectivos principais: 1. Incrementar o nível de consumo e resiliência da população que vive em situações de pobreza e vulnerabilidade; 2. Contribuir para o desenvolvimento do capital humano através da melhoria da nutrição, do acesso aos serviços básicos de saúde e educação do segmento da população que vive na pobreza e vulnerabilidade; 3. Prevenir e mitigar os riscos de violência, abuso, exploração, discriminação e exclusão social através dos serviços sociais e, 4. Desenvolver a capacidade institucional dos sectores governamentais que coordenam a segurança social básica. O Programa Conjunto foi estruturado em torno de um pacote coerente de intervenções, incluídas na ENSSB II e totalmente alinhadas ao Plano Operacional, em torno das 38 “Acções Estratégicas”, mas naquelas onde as agências da ONU têm mandato, capacidade de trabalho com parceiros governamentais visando fortalecer ainda mais o quadro de trabalho da Protecção Social. No decorrer do programa (2018-2019), as duas agências da ONU envolvidas (OIT e UNICEF) irão trabalhar com os parceiros a nível nacional, provincial e distrital para alcançar os seguintes resultados: 1. Até 2020, programas e políticas claras concebidos para operacionalizar a ENSSB II 2. Até 2020, evidências sólidas, advocacia e comunicação claras para as componentes principais da ENSSB II 3. Até 2020, o MGCAS tem reforçada a sua capacidade para coordenar e implementar a ENSSB II
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental; social protection / proteção social